Educación inclusiva - Cordero Aguilar, Heylen (2004)
Poverty is a characteristic in Latin American reality. In association to it, social exclusion, citizenship, economics, cultural and ethnic issues are present in Latin societies. Upon this exclusion, education plays a hoping part as a way to overcome the difficulties that limits human development. Costa Rica is a part of this reality. Multicultural aspects caused by foreign migration and social/cultural differences within costarricans generate exclusion. Inclusive education propose itself as a media to integrate all of these aspects, as a way to assure that both, rich and poor, can access human promotion. To include implies a wholesome vision and a reflexive look upon current curriculum, considered it within the social context.